Beyond Individual Ownership: Women’s and Men’s Land Tenure Rights in Iraqi Heritage Systems (Journal of Planner and Development, 2023)
This paper delves into the significant role played by local social and traditional structures in shaping Traditional Community Tenure (TCT) within Iraqi Land Tenure Legislation (ILTR), and examines their impact on gender inequalities, with a specific focus on women’s land tenure rights. The methodological approach employed in this study identified the sources of barriers to gender equality within TCT as outlined in ILTR at two different bilateral levels, with input obtained from key stakeholders in a selected city in Iraq. The case study survey encompassed three districts, which served as local layers within the historic sectors of the Iraqi city of Al-Nasiriya. the study employed quantitative methods, including a household surveyو within 3 residential neighborhoods; Al-Sharqiya, Al-Oroba, and Al-Zawiya. Out of the 420 copies of the survey distributed over Al-Nasiriya city.Despite the challenging circumstances caused by the COVID-19 pandemic, the obtained findings of this research contribute to the existing academic literature by evaluating gender disparities that extend beyond traditional property ownership patterns in Islamic forms of land tenure rights as outlined in current ILTR, serving as an introductory case in the Middle Eastern region. These findings shed light on the quality of sex-disaggregated land rights within the Iraqi context, which, in turn, influences access to productive resources for both women and men under ILTR.